From Carbon Accounting Quality to Green Investment: Moderated Mediation of Perceived Benefits and Access to Green Finance in Vietnamese Agriculture - Dao, Huy Manh; Dang, Mai Phuong (Research on World Agricultural Economy, 2026)
While carbon accounting is recognized as a pivotal environmental governance tool, prior literature has not explored in detail the mechanisms through which this informational resource translates into tangible investment decisions. This gap is particularly pronounced in emerging market contexts, which are characterized by multiple barriers regarding managerial cognition and capital availability. To address this knowledge gap, this study investigates the impact of carbon accounting quality within Vietnamese agricultural enterprises. Employing partial least squares structural equation modeling on survey data collected from 235 senior managers, the empirical analysis identifies carbon accounting quality as the main driver that exerts the strongest direct influence (β = 0.496). Beyond this direct pathway, information quality also has an indirect effect (β = 0.185) by enhancing the perceived benefits held by management. A critical and novel contribution of the research is the validation of the positive moderating role of access to green finance (β = 0.250). The availability of such capital functions as a vital catalyst that alleviates resource bottlenecks to significantly amplify the translation of perceived benefits into investment actions. With the model explaining 47.2% of the variance in investment decisions, the findings confirm that sustainable transition requires both internal information transparency and a supportive external financial ecosystem to provide a robust quantitative basis for green governance strategies. ER